Karakteristik Kuat Geser Tanah Dengan Tanpa Akar Vegetasi Pada Lereng Ruas Tawaeli -Toboli - Martini, M.; Sutapa, I.W.; Ramadhani, S. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
The contribution of vegetation to slope stability is based on hydrological and mechanical aspects. The effect of vegetation on the hydrological aspect is to reduce soil water content through transpiration, interception and evapotranspiration. And the mechanical influence of vegetation is through strengthening the roots in the soil. Water absorption by vegetation varies depending on age and density, rainfall factors and soil type. Cohesion (c) and friction angle () are soil shear strength parameters. In soil that has vegetation roots, it will form a composite material, namely the root-soil model, there is an increase in cohesion value with the presence of roots, this is what is called apparent cohesion (c'R). Several parameters that are believed to influence the shear strength of the soil and roots will also be studied, namely the physical properties of the roots, namely diameter, type of root/vegetation, and water content. For mechanical properties, namely the tensile strength of the roots, the shear strength parameters of the soil both without and with roots, namely cohesion, apparent cohesion and internal friction angle. The type of vegetation reviewed in this research is elephant grass with fibrous roots. The results obtained indirectly by increasing the value of cohesion and angle of friction in the soil due to the presence of roots influence/increase the shear strength of the soil. The volume of roots in the soil greatly influences changes in the cohesion value or angle of friction of the soil. As the root volume decreases, the shear strength value decreases, the shear strength parameter also decreases. In this study, the change in soil shear strength values in sandy soil conditions, the increase in cohesion value was not as significant compared to the change in friction angle values.